Contamination of Shale and Sandy Soils with Industrial Waste - Diyorova Muhabbat Khurramovna, Kuziev Jakhongir Madaminovich (International Journal of Modern Agriculture, 2021)
The Mubarak Gas Processing Facilities Plan (MGPP), located in the desert zone of Kashkadarya region, is one of the largest industrial faculties in the country, designed to extract sulfur from hydrocarbons rich, in hydrogen sulfide. As a result of these technological processes, large amounts of H2S and SO2compoundsare released into the environment as waste. As a result, under the influence of precipitation, these compounds act as a powder in dry conditions when they fall as acid rain. The effect of plant wastes on soil reclamation, based on the results of agrochemical research, having the amount of mobile nitrogen in irrigated sandy loam soils varied across the layers at the test sites and the effect on some heavy metals in the soil were also studied.